Student Acceptance of E-Learning during the COVID-19 Outbreak at Engineering Universities in Spain - Pedro Garrido-Gutiérrez; Teresa Sánchez-Chaparro; María Jesús Sánchez-Naranjo (MDPI AG, 2023)
This article analyses students' intention to use a particular e-learning technology (MS Teams) at university during the COVID-19 outbreak in Spain using the Unified Theory of Acceptance and Use of Technology (UTAUT). The model was refined through a qualitative analysis based on six focus group discussions with students from different engineering faculties in Madrid, Spain. A survey involving 346 undergraduate students was subsequently fed into the model. Structural Equation Modelling (SEM) and SMART PLS software were applied for data analysis. The results shed light on theoretical and practical implications. The model was validated by the data and displayed a high predictive ability. Social influence was found to have the greatest influence over students' acceptance, followed by the professor's role in shaping the perception of improvement. Facilitating conditions were found to be the least relevant factor, probably due to the particular context in which this study was conducted. A significant difference was found between the public and private institutions in terms of the importance of the perceived usefulness for the professor (this factor was more important for students' acceptance at the public university). In order to improve its acceptance and use under the current scenario, it is thus important for universities wishing to introduce e-learning to focus on creating a positive social environment around the e-learning platform, for example, by using social networks or relying on testimonies by professionals who could confirm the interest of such a platform in a future work environment. Understanding professors' perspective on the implementation of the platform is also of paramount importance. More research is also needed regarding context-related differences when analysing students' acceptance of e-learning.